(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1998)
A modification of recursion theorem in Cartesian linear combinatory algebras is proved which yields first order formalizability of theory of the last algebras. Some other improvements of this theory are demonstrated.